A new model with NEO PI-R for emotion simulations - Zhang, Yi; Li, Ling (Conference Publishing Services, 2013)
The last decade has witnessed an explosion of interest in research on human emotion modeling for generating intelligent virtual agents. This paper proposes a novel personality model based on the Revised NEO Personality Inventory (NEO PI-R). Compared to the popular Big-Five-Personality Factors (BIG5) model, our proposed model is more capable than BIG5 on describing a variety of personalities. Combining with emotion models it helps to produce more reasonable emotional reaction to external stimuli. A Resistant formulation is also proposed to effectively simulate the complicated negative emotions.